42 = 1*42 = 2*21 = 3*14 = 6*7

None of these factor pairs differ by 9, so the numbers will involve square roots. We can find them using the quadratic formula.

X(9-x) = -42

-x^2 + 9x = -42 (multiply it out)

x^2 - 9x - 42 = 0 (put the equation into standard form)

x = (-(-9) ±√((-9)^2 - 4(1)(-42)))/(2*1) (use the quadratic formula)

= (9 ±√(81+168))/2 (evaluate)

None of these factor pairs differ by 9, so the numbers will involve square roots. We can find them using the quadratic formula.

X(9-x) = -42

-x^2 + 9x = -42 (multiply it out)

x^2 - 9x - 42 = 0 (put the equation into standard form)

x = (-(-9) ±√((-9)^2 - 4(1)(-42)))/(2*1) (use the quadratic formula)

= (9 ±√(81+168))/2 (evaluate)

**= (9±√249)/2**(evaluate)**≈ {-3.3899, 12.3899}**